2016
DOI: 10.18549/pharmpract.2016.02.723
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of a pharmacist-led hypertension management service in primary care: outcomes and methodological challenges

Abstract: Background:Suboptimal utilisation of pharmacotherapy, non-adherence to prescribed treatment, and a lack of monitoring all contribute to poor blood (BP) pressure control in patients with hypertension.Objective:The objective of this study was to evaluate the implementation of a pharmacist-led hypertension management service in terms of processes, outcomes, and methodological challenges.Method:A prospective, controlled study was undertaken within the Australian primary care setting. Community pharmacists were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 34 publications
5
30
0
Order By: Relevance
“…Medication adherence practices are well promoted with focused group discussions. [31][32][33][34][35][36][37][38][39] Confidentiality and privacy should be maintained at all times during focused group discussions. Discussion between patients observed to be very fruitful.…”
Section: Focused Group Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication adherence practices are well promoted with focused group discussions. [31][32][33][34][35][36][37][38][39] Confidentiality and privacy should be maintained at all times during focused group discussions. Discussion between patients observed to be very fruitful.…”
Section: Focused Group Discussionmentioning
confidence: 99%
“…Physical verification of tablets/capsules in presence of healthcare professionals will certainly improve the understanding of the patient. [26][27][28][29][30][31][32][33][34][35][36][37][38]…”
Section: Train Patients In Clinics/hospitals For Medicine Consumptionmentioning
confidence: 99%
“…Pharmacist prescribing for patients with hypertension and diabetes mellitus was agreed upon by seven of the nine expert panel members and by 27 of the 31 hospital pharmacists who participated in the study. Collaborative pharmacist‐led management services in hypertension and diabetes mellitus can help to improve monitoring and control of blood pressure and blood glucose, CVD risk factors, medication adherence and optimise therapy …”
Section: Discussionmentioning
confidence: 99%
“…Collaborative pharmacist-led management services in hypertension and diabetes mellitus can help to improve monitoring and control of blood pressure and blood glucose, CVD risk factors, medication adherence and optimise therapy. [3,11,36,37] Results of the case studies showed that pharmacists and physicians prescribed similar treatment when the correct diagnosis was established. The case studies were selected as examples to demonstrate the ability of appropriate diagnosis by pharmacists even for 'atypical' cases.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, several health education programs have been initiated to improve blood pressure control in the community 13 and patients' knowledge on a disease and therapy, 14 including pharmacist led intervention in lifestyle changes and medication adherence among hypertensive patients. [15][16][17] A meta-analysis study showed that pharmacist led intervention was associated with significant reductions in systolic blood pressure [11 studies (2240 patients); −6.1 mmHg (95% confidence interval, −3.8 to−8.4 mmHg); P<0.00001]. 18 In addition, previous studies have demonstrated pharmacist led interventions can rationalise medication use in patients 19,20 and taking more positive role in patient self-management.…”
Section: Introductionmentioning
confidence: 99%